Saffron extract (Safr'Inside™) improves anxiety related behaviour in a mouse model of low-grade inflammation through the modulation of the microbiota and gut derived metabolites. Issue 23 (7th November 2022) - Pontifex, Matthew G.; Connell, Emily; Le Gall, Gwenaelle; Pourtau, Line; Gaudout, David; Angeloni, Cristina; Zallocco, Lorenzo; Ronci, Maurizio; Giusti, Laura; Müller, Michael; Vauzour, David
Abstract : Treatment of anxiety and depression predominantly centres around pharmacological interventions, which have faced criticism for their associated side effects, lack of efficacy and low tolerability. Abstract : Treatment of anxiety and depression predominantly centres around pharmacological interventions, which have faced criticism for their associated side effects, lack of efficacy and low tolerability. Saffron, which is reportedly well tolerated in humans, has been recognised for its antidepressant and anti-anxiety properties. Indeed, we previously reported upon the efficacy of saffron extract supplementation in healthy adults with subclinical anxiety. However, the molecular aetiology remains unclear. In a rodent model of low-grade chronic inflammation, we explored the impact of a saffron extract (Safr'Inside™) supplemented at a physiological dose, which equated to 22 ± 1.2 mg per day human equivalent dose for a person of 60 kg. Behavioural tests (Open Field task, Y maze, Novel object recognition), caecal 16S rRNA microbial sequencing, caecal 1 H NMR metabolomic analysis and 2DE brain proteomic analyses were completed to probe gut–brain axis interactions. Time occupying the centre of the Open Field maze (OF) was increased by 62% in saffron supplemented animals. This improvement in anxiety-related behaviour coincided with gut microbial shifts, notably Akkermansia, Muribaculaceae, Christensenellacae and Alloprevotella which significantly increased in response to saffron supplementation. Akkermansia and Muribaculaceae abundance negatively correlated with the neurotoxic metabolite dimethylamine which was reduced in saffron supplemented animals. Brain proteomic analysis highlighted several significantly altered proteins including ketimine reductase mu-crystallin which also correlated with dimethylamine concentration. Both dimethylamine and ketimine reductase mu-crystallin were associated with OF performance. This may be indicative of a novel interaction across the gut–brain axis which contributes to anxiety-related disorders.